2015
DOI: 10.3109/14767058.2015.1086742
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 long-chain polyunsaturated fatty acids and fish oil supplementation during pregnancy: which evidence?

Abstract: There was not enough evidence to support the routine use of omega-3 supplementation during pregnancy. Given the 73% significant decrease in perinatal death in the singleton gestations who started omega-3 supplementation ≤ 20 weeks, further research is needed. Large RCTs in multiple gestations and longer follow-up are also required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 58 publications
0
46
1
3
Order By: Relevance
“…Different strategies have been adopted for prevention of SPTB, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] including progesterone 16,22 and cerclage, 17,18 as well as lifestyle modification such as smoking cessation, 23 diet and aerobic exercise, 24 and nutritional supplements, [25][26][27][28][29][30] including omega-3, 25-28 folic acid, 29 and vitamins. 30 The evidence supports the use of vaginal progesterone in singleton pregnancies with short cervix, 16 while cervical cerclage seems to be beneficial only in the subgroup of women with both prior SPTB and TVU CL 25 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strategies have been adopted for prevention of SPTB, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] including progesterone 16,22 and cerclage, 17,18 as well as lifestyle modification such as smoking cessation, 23 diet and aerobic exercise, 24 and nutritional supplements, [25][26][27][28][29][30] including omega-3, 25-28 folic acid, 29 and vitamins. 30 The evidence supports the use of vaginal progesterone in singleton pregnancies with short cervix, 16 while cervical cerclage seems to be beneficial only in the subgroup of women with both prior SPTB and TVU CL 25 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies have been adopted for prevention of SPTB, including progesterone and cerclage, as well as lifestyle modification such as smoking cessation, diet and aerobic exercise, and nutritional supplements, including omega‐3, folic acid, and vitamins …”
Section: Commentmentioning
confidence: 99%
“…Previous research warranted future studies including children of multiple gestations. (81) Our analyses examined twins in addition to singletons and independently.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors reported a positive effect of supplementation on neonatal outcome of patients with gestational diabetes (hyperbilirubinemia rate, hospitalization rate) as well as a significant reduction in perinatal death in singleton pregnancies supplemented before 20 weeks of gestation [65].…”
Section: Discussionmentioning
confidence: 99%